2019
DOI: 10.15666/aeer/1702_32933303
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Edta-Se With Different Concentrations on Photosynthesis of Fragrant Rice (Oryza Sativa L.)

Abstract: Selenium (Se), as an essential element, has its effects on the growth and development of plants. Present study aimed to assess Se mediated chlorophyll contents, net photosynthesis, biomass accumulation and activity of carbon metabolism enzymes. Three different levels of Ethylenediamine tetra acetic acid -chelating Se (EDTA-Se) at 10(E1), 30(E2) and 50(E3) μmol L -1 were overhead applied at initial heading stage of two aromatic rice cultivars i.e., Xiangyaxiangzhan and Meixiangzhan2, the treatment without Se we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Current study agreed with the study of Kong et al (2017) which indicated that the photosynthetic rate at grain-filling stage is one of the important factors affecting the yield of aromatic rice. Our result was also consistent with the study of Lai et al (2019) who indicated that exogenous Se applications could increase the rice yield by regulating the photosynthesis.…”
Section: Discussionsupporting
confidence: 93%
“…Current study agreed with the study of Kong et al (2017) which indicated that the photosynthetic rate at grain-filling stage is one of the important factors affecting the yield of aromatic rice. Our result was also consistent with the study of Lai et al (2019) who indicated that exogenous Se applications could increase the rice yield by regulating the photosynthesis.…”
Section: Discussionsupporting
confidence: 93%
“…The investigations of Liu et al (2019) and Kong et al (2017) demonstrated that the seed-setting rate and 1,000-grain weight of rice were largely dependent on the photosynthesis during the grain-filling stage and that the unsuitable environment during this phase would cause the decline of grain yield due to lower seed-setting rate and 1,000-grain weight. An early study has evidenced that the application of Se at heading stage improved grain yield of rice by enhancing the photosynthesis during the grain-filling stage (Lai et al, 2019). Our results agreed with the study of Duan et al (2019), who indicated that application of the appropri-ate amount of Se increased rice yield by delaying leaf senescence and enhancing photosynthesis.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the research of He [15] revealed that application of Selenite application at rupturing stage significantly increased the grain yield of rice and promoted the activities of peroxidase (POD), superoxide dismutase (SOD) and catalase (CAT) in leaves. Lai [16] demonstrated that that exogenous Se applications could increase the rice yield by regulating the photosynthesis. Furthermore, Wang [17] indicated that lower Se treatments could activate antioxidant system and enhance photosynthesis while higher Se treatment damaged photosynthesis apparatus and inhibited photosynthesis.…”
Section: Introductionmentioning
confidence: 99%